Studi Tentang Pola Asuh Orang Tua Dalam Tumbuh Kembang Anak - Jenny I. Dengah (Peneliti.net, 2022)
Parenting style is a series of attitudes that are applied to children as a way to discipline children so that the parenting style given by parents to their children greatly influences the child's personality and behavior. Parents as family members are the first pillar of education in the process of developing a child's life. The problem in this study is formulated: What is the parenting style of parents in the growth and development of children in Malalayang I Timur District VI, Manado City? The purpose of this study was to: find out how parents care for children's growth and development in everyday life in Malalayang I East District VI Environment Manado City. This study used qualitative research methods. The main informants are the three heads of families, namely a mother and a father. Data collection was carried out through observation techniques, interviews, and documentation studies where the researcher served as the main tool. Data were analyzed using the Miles and Huberman method (Sugiyono 2012:247). From the results of the study it was concluded that the parenting styles of parents in Malalayang I Timur District VI, Manado City, differ, there are permissive, democratic parenting styles, there are also parenting styles for children with autism, but in general all parents want their children to grow and develop. according to expectations both physically and mentally.